PENINGKATAN KINERJA MELALUI STRATEGI BENCHMARKING - Aswadi Lubis (Institut Agama Islam Negeri Padangsidimpuan, 2016)
Benchmarking will actually encourage us to look deep into the processes of our competitors (or associate us) similar, perhaps better implemented and proven to deliver results or output quality better. Also benchmarking can help to get a shortcut to reach the goal (target), by imitating so many things can be saved, among other things we can further shorten the learning process (learning process), reducing the likelihood of failure because it can learn from the failures and mistakes of others. Strategies benchmarking in improving the performance of the company / organization conducted a comprehensive manner through: 1) adjustment of the vision, mission and objectives, 2) strategic environmental analysis, 3) determine the topic of benchmarking, 4) determine the company's superior goal benchmarking, and 5) form a team of benchmarking. The implementation of benchmarking study on company objectives using interviews / discussions, observation, and documentation to collect data. Data from the benchmarking study further adapted and selected by considering several factors, among them; culture, human resource capacity and budgeting by adhering to the principle of Keep preserve old things are good and taking things that new and better.